Fadeaway girl : a novel - Grimes, Martha (Viking, 2011)
Emma Graham continues her investigation into the disappearance of the Slade baby from the Belle Ruin Hotel more than 20 years before. The sudden appearance in town of the baby's father makes her even more determined to learn the truth.